Water scavenger beetles (Coleoptera: Hydrophilidae) from Bingöl province of Turkey - Mart, Abdullah; Erman, Orhan (University of Punjab (new Campus), 2017)
Twenty nine species and 2 subspecies belonging to 10 genera of water scavenger beetles (Coleoptera: Hydrophilidae) collected from Bingöl province between May 2003-October 2004 have been described. Copyright 2017 Zoological Society of Pakistan.
Keywords: Coleoptera; Hydrophilidae; Water scavenger beetles